2006
DOI: 10.1111/j.1469-7998.2006.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of juvenile terrestrial salamanders to introduced (Lithobius forficatus) and native centipedes (Scolopocryptops sexspinosus)

Abstract: When introduced species invade ecosystems, alterations in community structure can emerge from the competitive and predatory interactions that occur between introduced and native guild members. Because a number of recent studies have shown that large predatory invertebrates can both compete with and prey on small vertebrates and because introductions of non-native species may play a role in amphibian declines, the effects of introduced centipedes Lithobius forficatus and native centipedes Scolopocryptops sexspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…For example, behavioural indices have been used to determine if a salamander displays submissive or dominant agonistic behaviours in response to competitor, mate, predator, and prey cues (Jaeger 1984). Previous investigations have shown that P. cinereus responds aggressively to invertebrate guild members, such as centipedes (Hickerson et al 2004;Anthony et al 2007) and beetles (Gall et al 2003). It is possible that aggressive behaviour toward earthworms could be occurring if salamanders mistake worms for guild members.…”
Section: Discussionmentioning
confidence: 99%
“…For example, behavioural indices have been used to determine if a salamander displays submissive or dominant agonistic behaviours in response to competitor, mate, predator, and prey cues (Jaeger 1984). Previous investigations have shown that P. cinereus responds aggressively to invertebrate guild members, such as centipedes (Hickerson et al 2004;Anthony et al 2007) and beetles (Gall et al 2003). It is possible that aggressive behaviour toward earthworms could be occurring if salamanders mistake worms for guild members.…”
Section: Discussionmentioning
confidence: 99%
“…If prey exhibiting innate predator recognition are unable to acquire recognition of novel predatory stimuli, they may not respond adaptively to non‐native predatory threats (Kiesecker & Blaustein 1997; Pearl et al. 2003; Anthony et al. 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Determining the role of experience in predator recognition is especially important for native prey in habitats where predators have been introduced. If prey exhibiting innate predator recognition are unable to acquire recognition of novel predatory stimuli, they may not respond adaptively to nonnative predatory threats (Kiesecker & Blaustein 1997;Pearl et al 2003;Anthony et al 2007). This has been described as a primary cause of native amphibian population declines and extinctions in some habitats where non-native predators have been introduced (Knapp & Matthews 2000;Adams et al 2001;Pilliod & Peterson 2001;Kats & Ferrer 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We used the methodology of Anthony et al (2007) to assess the ability of S. sexspinosus and P. stygicus to displace one another in a structurally simple environment. We constructed arenas with low (dry portion of the arena), intermediate (dampened filter paper covering a portion of the arena floor), and high-quality microhabitats (dampened filter paper and space beneath artificial cover; Fig.…”
Section: Co-occurrence Beneath Cover In the Field And Laboratorymentioning
confidence: 99%
“…We placed either a single centipede, a single beetle, or one individual of each species into arenas, and after 24 h, the locations of individuals in nine interspecific pairs were compared to locations of nine solitary individuals of each species. In the absence of interference, individuals are expected to gain access to high-quality habitat (Anthony et al 2007). In interspecific trials, we predicted that, if competition were occurring for high-quality space, competitively dominant individuals would gain access to the highest quality microhabitat in laboratory arenas.…”
Section: Co-occurrence Beneath Cover In the Field And Laboratorymentioning
confidence: 99%